Evaluasi Incident Management Dan Problem Management Sistem Informasi Manajemen Rumah Sakit (SIMRS) Pada Rumah Sakit Umum Daerah Kanjuruhan Kabupaten Malang Menggunakan Framework ITIL V3 - Athayya Salsabila Anandityo; Yusi Tyroni Mursityo; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Kanjuruhan Regional General Hospital, is one of the organizations in the health services that has utilized information technology as the main support for its business processes. One of the supports is the Hospital Management Information System (SIMRS) which integrates modules in hospitals such as outpatient, inpatient, pharmacy, medical records, and others. SIMRS is implementing the best practices in Minister of Health Regulation No. 82 of 2013 but still not done well. Accordingly, an evaluation is needed to improve the IT service management. The absence of clear procedures related to how to handle incidents and problems with IT services, especially in SIMRS, causes handling can not be done directly, considering that there are so many disruptions that affect service performance. This study uses the ITIL V3 framework that focuses on the Incident Management and Problem Management processes. The analysis results obtained in both processes are in level 2 Repeatable level which means that some activities related to incident management have been carried out but there are still no standard rules as the basis for the implementation of these activities. So as to achieve the expected value the researchers compiled recommendations to improve IT service management, especially on SIMRS services. The recommendations focus on describing the activities that should be carried out and making documentation in order to reach the expected level.